Composite Materials and Bioimplants

The composite material of titanium fluoride and titanium addresses the challenge of combining antibacterial properties with high hardness by utilizing a crystalline phase of titanium fluoride within the material, resulting in enhanced durability and resistance to bacterial growth in biological implants.

JP7663665B2Active Publication Date: 2025-04-16KYOCERA CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023205780
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-06-01
Filing Date
2023-12-06
Publication Date
2025-04-16
Estimated Expiration
2039-05-30

AI Technical Summary

Technical Problem

Existing metallic materials with surface-implanted fluorine ions do not effectively combine antibacterial properties with high hardness and wear resistance, particularly in biological implants.

Method used

A composite material comprising a crystalline phase of titanium fluoride and a metallic phase of titanium, where the crystalline phase is located deeper than the surface, enhancing antibacterial properties and hardness through covalent bonding and lattice distortions.

Benefits of technology

The composite material achieves significant antibacterial properties and high hardness, effectively resisting bacterial growth and wear, thereby enhancing the durability and longevity of biological implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663665000002
    Figure 0007663665000002
  • Figure 0007663665000003
    Figure 0007663665000003
  • Figure 0007663665000004
    Figure 0007663665000004
Patent Text Reader

Abstract

To provide a composite material and a bioimplant.SOLUTION: A composite material includes a crystal phase of titanium fluoride and a metal crystal phase of titanium. The crystal phase of the titanium fluoride is present in a first region located away from the surface in the depth direction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to composite materials and biological implants. [Background technology]

[0002] Metal materials having surfaces implanted with fluorine ions are known (see, for example, Patent Document 1 and Non-Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4568396 [Non-patent literature]

[0004] [Non-Patent Document 1] M. Yoshinari, Y. Oda, T. Kato, K. Okuda, "Influence of surface modifications to titanium on antibacterial activity in vitro", Biomaterials, 2001, 22, p. 2043-2048 Summary of the Invention

[0005] According to one embodiment, the composite material has a titanium fluoride crystalline phase and a titanium metallic crystalline phase, the titanium fluoride crystalline phase being present in a first region located away from the surface in the depth direction.

[0006] A biological implant according to an embodiment includes a composite material according to an embodiment. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a schematic diagram illustrating a composite material according to one embodiment. [Diagram 2]FIG. 2 is an example of a biological implant according to one embodiment. [Diagram 3] FIG. 3 is a graph showing the measurement results of the fluorine concentration in the examples. [Figure 4] FIG. 4 is a graph showing the results of hardness measurements in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] <Composite materials> Hereinafter, a composite material according to an embodiment will be described in detail with reference to the drawings. However, for the sake of convenience, the drawings referred to below show only the configurations necessary for explaining the embodiment in a simplified form. Therefore, the composite material according to an embodiment may have any configurations not shown in the drawings referred to. Furthermore, the dimensions of the configurations in the drawings do not faithfully represent the dimensions and dimensional ratios of the actual configurations. These points also apply to the biological implant described below.

[0009] Fig. 1 is a schematic diagram showing a composite material according to one embodiment, in which a cross section of a portion including a surface of the composite material is shown in an enlarged scale.

[0010] Composite material 1 contains titanium (Ti) and fluorine (F), and has a titanium fluoride crystalline phase 2 (hereinafter sometimes referred to as "crystalline phase 2") and a titanium metal crystalline phase 3 (hereinafter sometimes referred to as "metal crystalline phase 3"). In crystalline phase 2, titanium fluoride, a compound of titanium and fluorine, exists in a crystalline state. In metal crystalline phase 3, titanium exists in a crystalline state formed by metallic bonds.

[0011] As described above, the composite material 1 contains fluorine and has the crystal phase 2, and therefore is able to exhibit antibacterial properties due to fluorine. In addition, the composite material 1 has a high hardness, and therefore is able to exhibit excellent abrasion resistance, etc. The reason why the composite material 1 has a high hardness is presumed to be as follows.

[0012] The bond between titanium and fluorine in titanium fluoride is a covalent bond. Therefore, the crystalline phase 2 functions as an obstacle to the transition moving through the metal crystalline phase 3. Therefore, when the composite material 1 has the crystalline phase 2, the amount of energy required for the transition to move increases, and as a result, the hardness of the composite material 1 increases. Note that as the fluorine concentration in the composite material 1 increases, the proportion of the crystalline phase 2 tends to increase.

[0013] Examples of titanium fluorides include TiF (titanium fluoride) and TiF 2 (Titanium difluoride), TiF 3 (Titanium trifluoride), TiF 4 (Titanium tetrafluoride), TiOF (Titanium oxyfluoride), TiOF 2 (Titanium Oxydifluoride) or F-TiO 2 (fluorine-doped titanium oxide). Titanium fluoride is TiOF 2 The crystalline phase 2 may have a Ti-F-Ti bond (covalent bond).

[0014] Methods for measuring the crystal structure include, for example, a transmission electron microscope (hereinafter, sometimes referred to as "TEM"), X-ray diffraction (hereinafter, sometimes referred to as "XRD"), and X-ray photoelectron spectroscopy (hereinafter, sometimes referred to as "XPS"), etc.

[0015] The composite material 1 may include a region (first region) 12 that includes a surface 11 of the composite material 1 and has a predetermined thickness in a depth direction from the surface 11. The first region 12 is a composite phase of titanium and fluorine. The fluorine concentration of the first region 12 may be 1 ppm or more.

[0016] The thickness T of the first region 12 is, for example, 30 to 800 nm. When a numerical range is indicated using "to", it is assumed that the lower and upper limits are included unless otherwise specified. For example, when the numerical range is 30 to 800 nm, the lower limit indicates 30 nm or more and the upper limit indicates 800 nm or less.

[0017] The crystalline phase 2 may be located within the first region 12. When such a configuration is satisfied, the crystalline phase 2 is located near the surface 11, and therefore, the antibacterial properties due to the fluorine of the titanium fluoride are enhanced, and the hardness of the surface 11 and its vicinity can be increased.

[0018] The crystal phase 2 may be located in a region having a depth of 20 to 200 nm from the surface 11. The depth may be determined based on the surface 11.

[0019] The metal crystalline phase 3 may have a first phase 31 containing fluorine (fluorine-containing phase). In other words, the metal crystalline phase 3 may have a first phase 31 containing fluorine in the titanium crystal lattice. In the first phase 31, fluorine may be introduced as an interstitial element in the titanium crystal lattice. If the metal crystalline phase 3 has the first phase 31, the hardness of the composite material 1 can be increased. The following reasons are presumed to be the reasons for this.

[0020] In the first phase 31, the fluorine atoms penetrate into the spaces in the titanium crystal lattice formed by metallic bonds. This causes lattice distortion in the titanium crystal according to the size of the penetrated fluorine atoms. The deformation of the titanium crystal lattice is caused by the movement of dislocations, which are defects in the crystal lattice. If the titanium crystal lattice is distorted by the penetration of fluorine atoms, the mobility of dislocations decreases, and as a result, the hardness of the composite material 1 increases. Therefore, if the metal crystal phase 3 has the first phase 31, the first phase 31, in addition to the crystal phase 2, also contributes to the hardness of the composite material 1, so that the hardness of the composite material 1 can be increased. In addition, when the fluorine concentration in the composite material 1 is reduced, the proportion of the first phase 31 tends to increase.

[0021] The first phase 31 may be located in the first region 12. When such a configuration is satisfied, the first phase 31 is located near the surface 11, and therefore the hardness of the surface 11 and its vicinity can be increased. In addition, the first region 12 in which the first phase 31 is located is the same as the first region 12 in which the crystal phase 2 is located. This also applies to the first region 12 in which the second phase 32 described later is located, the first region 12 in which the maximum value of the fluorine concentration is located, and the first region 12 in which the maximum value of the hardness is located. That is, the first regions 12 in the description of each configuration are all the same as each other.

[0022] The metal crystal phase 3 may further have a second phase 32 (fluorine-free phase) that does not contain fluorine and is located more inward than the first phase 31. When such a configuration is satisfied, a portion including the first phase 31 located closer to the surface 11 than the second phase 32 is less likely to be damaged. Specifically, the second phase 32 has higher toughness than the first phase 31 due to not containing fluorine. Therefore, when an impact is applied to the surface 11, the impact can be absorbed by the second phase 32 that has a relatively high toughness. As a result, a portion including the first phase 31 located closer to the surface 11 than the second phase 32 is less likely to be damaged.

[0023] The second phase 32 being located inward of the first phase 31 means that the second phase 32 is located farther from the surface 11 than the first phase 31. Inward means the inside of the composite material 1 with respect to the surface 11. In other words, inward means the direction of increasing depth in the composite material 1. Also, not containing fluorine means a state in which fluorine is substantially not contained and there is substantially no effect of fluorine. Specifically, it may be determined that the fluorine is not contained when the fluorine concentration is less than 1 ppm.

[0024] The second phase 32 may be located more inward than the first region 12. When such a configuration is satisfied, the first region 12 located closer to the surface 11 than the second phase 32 becomes less susceptible to damage due to the second phase 32 having a relatively high toughness.

[0025] The composite material 1 may further include a region (second region) 13 located inward from the first region 12. The second region may be a region that contains titanium and does not contain fluorine. The second phase 32 may be located within the second region. The second region 13 may be in contact with the first region 12. In other words, the first region 12 and the second region 13 may be continuous regions in the composite material 1.

[0026] The metal crystal phase 3 may contain, for example, a titanium-based metal. Examples of titanium-based metals include pure titanium and titanium alloys. Examples of pure titanium include industrially pure titanium such as CP2 titanium, which has a titanium matrix. Titanium alloys are alloys with titanium as the matrix, and examples of such alloys include Ti-6Al (aluminum)-4V (vanadium), Ti-15Mo (molybdenum)-5Zr (zirconium)-3Al, Ti-Nb (niobium), Ti-6Al-7Nb, Ti-6Al-2Nb-1Ta (tantalum), Ti-30Zr-Mo, Ni (nickel)-Ti, Ti-3Al-2.5V, Ti-10V-2Fe (iron)-3Al, or Ti-15V-3Cr (chromium)-3Al-3Sn (tin).

[0027] The composite material 1 may further include a non-crystalline phase 4 (amorphous phase) containing titanium and fluorine. When such a constitution is satisfied, the composite material 1 becomes difficult to be damaged due to the high toughness of the non-crystalline phase 4.

[0028] The amorphous phase 4 may be located within the first region 12. When such a configuration is satisfied, the first region 12 becomes difficult to be damaged due to the high toughness of the amorphous phase 4.

[0029] The composite material 1 may further have a mixed phase 5 containing an amorphous phase 4, a crystalline phase 2, and a metal crystalline phase 3 (first phase 31). In one embodiment, the mixed phase 5 is located in the first region 12. In the mixed phase 5, a plurality of amorphous phases 4, crystalline phases 2, and metal crystalline phases 3 are mixed. In this case, the material properties of each phase are different, but the material properties of the composite material 1 in the first region 12 are properties according to the ratio of each phase. Specifically, the material properties of each phase contained are average properties or properties close to the average properties. That is, by containing each phase as the mixed phase 5, the composite material 1 can reduce the portion with different material properties in the first region. Therefore, by having the mixed phase 5, the composite material 1 can reduce the possibility that the material partially peels off from the first region 12. That is, the stability of the composite material 1 can be improved.

[0030] In the composite material 1, the fluorine concentration may have a maximum value on the inside of the surface 11 (see FIG. 3). When such a configuration is satisfied, when a new surface 11 is exposed due to wear or the like, the surface 11 having a relatively high fluorine concentration is likely to be exposed, and therefore antibacterial properties are likely to be exhibited for a long period of time.

[0031] The fluorine concentration may increase from the surface 11 toward the inside, reaching a maximum value (see FIG. 3). In other words, the fluorine concentration may increase and reach a maximum value as the depth increases. If such a configuration is satisfied, when a new surface 11 is exposed due to wear or the like, a surface 11 having a relatively high fluorine concentration is exposed, and therefore it is possible to exhibit antibacterial properties over a long period of time. Furthermore, by adjusting the distribution of the fluorine concentration, the time when the composite material 1 exhibits antibacterial properties can be adjusted.

[0032] The maximum value of the fluorine concentration may be located within the first region 12. When such a configuration is satisfied, the maximum value of the fluorine concentration is located close to the surface 11, thereby enhancing antibacterial properties.

[0033] The maximum value of the fluorine concentration may be located closer to the surface 11 than the central portion 12a in the thickness direction A of the first region 12 (see FIGS. 1 and 3). When such a configuration is satisfied, the maximum value of the fluorine concentration is located closer to the surface 11, thereby enhancing antibacterial properties.

[0034] Here, the concentration in the fluorine concentration refers to atomic concentration. In one embodiment, the fluorine concentration refers to the number of fluorine atoms per unit volume relative to the sum of the ideal number of titanium atoms and the number of fluorine atoms per unit volume. Examples of methods for measuring the fluorine concentration include secondary ion mass spectrometry (hereinafter sometimes referred to as "SIMS") and XPS. SIMS is suitable when the fluorine concentration is relatively low. XPS is suitable when the fluorine concentration is relatively high.

[0035] The maximum value of the fluorine concentration is, for example, 10 to 80 atomic %. The fluorine concentration in a region less than 5 nm deep from the surface 11 is, for example, 0.5 to 20 atomic %. The fluorine concentration in a region 5 nm or more and less than 20 nm deep is, for example, 2 to 30 atomic %. The fluorine concentration in a region 20 nm or more and less than 50 nm deep is, for example, 5 to 80 atomic %. The fluorine concentration in a region 50 nm or more and 100 nm deep is, for example, 2 to 80 atomic %.

[0036] The hardness of the composite material 1 may have a maximum value inward from the surface 11 (see FIG. 4). When such a configuration is satisfied, when a new surface 11 is exposed due to wear or the like, the surface 11 having a relatively high hardness is likely to be exposed, increasing the possibility that the surface 11 will maintain a high hardness over a long period of time. Note that the surface 11 in the explanation of the hardness is the same as the surface 11 in the explanation of the fluorine concentration described above.

[0037] The hardness may increase from the surface 11 toward the inside, reaching a maximum value (see FIG. 4). In other words, the hardness may increase and reach a maximum value as the depth increases. When such a configuration is satisfied, when new surface 11 is exposed due to wear or the like, a surface 11 having a relatively high hardness is exposed, and therefore surface 11 will maintain a high hardness over a long period of time.

[0038] Alternatively, the hardness may increase from the surface 11 toward the inside, reach a maximum value, and then decrease further toward the inside (see FIG. 4). In other words, the composite material 1 may be configured so that the hardness changes gradually inside. This can reduce the occurrence of local stress compared to a configuration in which the hardness changes suddenly inside the composite material 1, thereby reducing the possibility of the first region 12 peeling off.

[0039] The maximum value of the hardness may be located within the first region 12. When such a configuration is satisfied, the maximum value of the hardness is located near the surface 11, so that the hardness of the surface 11 and its vicinity can be increased.

[0040] The maximum value of the hardness may be located closer to the surface 11 than the central portion 12a in the thickness direction A of the first region 12 (see Figs. 1 and 4). When such a configuration is satisfied, the maximum value of the hardness is located closer to the surface 11, so that the hardness of the surface 11 and its vicinity can be increased.

[0041] The maximum value of hardness may be located closer to surface 11 than the maximum value of fluorine concentration (see Figs. 3 and 4). When such a configuration is satisfied, the hardness of the portion located closer to surface 11 than the maximum value of fluorine concentration becomes relatively large. Therefore, the portion located closer to surface 11 than the maximum value of fluorine concentration is less likely to be damaged by wear or the like, and it becomes possible to exhibit antibacterial properties over a long period of time.

[0042] The hardness is, for example, 3 to 10 GPa. The maximum value of the hardness is, for example, 5 to 10 GPa. The hardness is an indentation hardness, which indicates how difficult it is for the surface 11 to deform. The hardness is calculated from the indentation depth and the force required when an indenter is pressed into the surface 11. Specific methods for measuring the hardness include, for example, a nanoindentation method (compliant with ISO 14577).

[0043] The composite material 1 may further include an oxide film (not shown) located on the outermost surface. In this case, the surface 11 of the composite material 1 is made of the surface of the oxide film. The thickness of the oxide film is, for example, 2 to 5 nm. The composition of the oxide film is, for example, TiO 2 (titanium dioxide) and the like. The oxide film may contain fluorine. The oxide film is formed, for example, by an oxidation treatment. Examples of the oxidation treatment include natural oxidation, heat treatment, oxygen plasma treatment, immersion in an acid solution, and anodization.

[0044] In the composite material 1, the titanium content may be greater than the fluorine content. Furthermore, the composite material 1 may contain titanium as a main component. The main component refers to a component that is contained in the composite material 1 in the largest amount by mass ratio.

[0045] <Method of manufacturing composite materials> Next, a method for producing a composite material according to one embodiment will be described in detail, taking as an example the case of obtaining the above-mentioned composite material 1.

[0046] First, a titanium-based metal is prepared. The titanium-based metal may be washed as necessary. For example, an organic solvent may be used for washing. Examples of the organic solvent include ethanol and acetone. The organic solvents exemplified above may be used in combination. Washing may be performed by applying ultrasonic waves. After washing, the titanium-based metal may be vacuum-dried in a desiccator, for example.

[0047] Next, fluorine ions are implanted into the surface of the titanium-based metal to obtain the composite material 1. The conditions for implanting the fluorine ions include, for example, the following conditions. Implantation energy: greater than 30 keV and less than 80 keV Injection dose: 1×10 16 ~5×10 17 atoms / cm 2 (atom / cm 2 )

[0048] The obtained composite material 1 may be washed as necessary. The washing conditions may be the same as those exemplified for the titanium-based metal described above. After washing, the composite material 1 may be vacuum-dried in a desiccator, for example.

[0049] In the above-described embodiment, an example has been described in which composite material 1 is obtained by injecting fluorine ions. However, the method for producing composite material 1 is not limited to this, and methods other than injecting fluorine ions can be used as long as composite material 1 is obtained.

[0050] <Bioimplants> Next, a biological implant according to an embodiment will be described in detail with reference to the drawings. In this embodiment, a dental implant will be described as an example of the biological implant.

[0051] FIG. 2 is a schematic diagram showing the appearance of a dental implant according to one embodiment.

[0052] The dental implant 100 comprises a fixture 101, an abutment 102 attached to an end of the fixture 101, and an artificial tooth 103 attached to the fixture 101 via the abutment 102.

[0053] In the dental implant 100, each of the fixture 101, the abutment 102, and the artificial tooth 103 contains the composite material 1. As described above, since the composite material 1 has antibacterial properties and high hardness, the dental implant 100 can inhibit bacterial growth and exhibit excellent durability against brushing, repeated use, cleaning, and the like.

[0054] Here, each of the fixture 101, the abutment 102, and the artificial tooth 103 may be composed of only the composite material 1. Also, a part of these may be composed of the composite material 1, and the remaining part may be composed of a material other than the composite material 1. Also, at least one of the fixture 101, the abutment 102, and the artificial tooth 103 may contain the composite material 1, and the other members may contain a material other than the composite material 1. With the above-mentioned configuration, the proliferation of bacteria on the implant surface is suppressed. For example, since the fixture 101 and the abutment 102 are used in an oxygen-deficient environment, the proliferation of anaerobic bacteria can be expected to be suppressed. Also, for example, since the artificial tooth 103 is exposed to air in the oral cavity, the proliferation of facultative anaerobic bacteria and aerobic bacteria can be expected to be suppressed. Therefore, the composite material 1 may be appropriately used for the fixture 101, the abutment 102, and the artificial tooth 103 according to the type of bacteria to be suppressed and the required antibacterial performance.

[0055] The first region 12 in the composite material 1 may be located, for example, in a portion of the dental implant 100 where bacteria may come into contact, or where wear may occur. For example, the dental implant 100 may be configured so that the first region 12 is located on the surfaces of the fixture 101, the abutment 102, and the artificial tooth 103. Also, for example, the dental implant 100 may be configured so that the first region 12 is located at each of the joints of the fixture 101, the abutment 102, and the artificial tooth 103. This point is similar to other biological implants and other members other than biological implants, which will be described later.

[0056] While one embodiment of the present disclosure has been illustrated above, it goes without saying that the present disclosure is not limited to the above-described embodiment, and any embodiment may be used without departing from the gist of the present disclosure.

[0057] For example, in the above embodiment, the biological implant is described as a dental implant, but the biological implant is not limited thereto. For example, the biological implant may be an implant made of a biological metal such as titanium. Other biological implants include artificial joints such as femoral stems or acetabular shells, and spinal surgical implants such as spinal fixation instrumentation.

[0058] In the above-mentioned embodiment, the composite material 1 is used for a biological implant, but the composite material 1 is not limited to being used for a biological implant. In other words, the composite material 1 may be used as a material for a component that requires antibacterial properties and high hardness. Examples of other components include orthodontic wires, surgical instruments, injection needles, eyeglass frames, tableware, food factory lines, water bottle openings, kitchen knives, toilets, Washlets (registered trademark), faucets, and water and sewer pipes.

[0059] The present disclosure will be described in detail below with reference to examples. Note that the present disclosure is not limited to the following examples. EXAMPLES

[0060] [Examples 1 and 2] <Preparation of composite materials> First, the following test pieces were prepared. Test piece: 1mm thick pure titanium made of CP2 type titanium

[0061] The above-mentioned test pieces were molded into disks with a diameter of 14 mm and a thickness of 1 mm, then ultrasonically cleaned with ethanol and acetone, and vacuum dried in a desiccator. Fluorine ions were then implanted into the surfaces of the test pieces under different conditions to obtain composite materials 1 of Examples 1 and 2.

[0062] The conditions for implanting fluorine ions are as follows: Example 1 Implantation energy: 40 keV Injection dose: 5×10 17 atoms / cm 2 Example 2 Implantation energy: 40 keV Injection dose: 5×10 16 atoms / cm 2

[0063] The obtained composite material 1 was ultrasonically cleaned with ethanol and acetone, vacuum dried in a desiccator, and then used for evaluation.

[0064] [Comparative Example 1] Comparative Example 1 was a test piece similar to those in Examples 1 and 2, but into which fluorine ions were not implanted.

[0065] <Evaluation> The fluorine concentration, hardness, and crystal structure were measured for the composite material 1 of Examples 1 and 2. The antibacterial property was also measured for the composite material 1 of Example 1. For Comparative Example 1, the hardness and antibacterial property were measured.

[0066] FIG. 3 is a graph showing the measurement results of the fluorine concentration in Examples 1 and 2.

[0067] (Fluoride concentration) The fluorine concentrations in Examples 1 and 2 were measured by XPS and SIMS. Specifically, in the region where the fluorine concentration was relatively high and exceeded the measurement range of SIMS, the fluorine concentration was measured by XPS, and in the other regions, the fluorine concentration was measured by SIMS. Specifically, in the range where the fluorine concentration was up to 10 atomic %, the fluorine concentration was measured by SIMS. In addition, in the range where the fluorine concentration was 10 atomic % or more, the fluorine concentration was measured by XPS. Here, the XPS measurement was performed at a depth of 0 to 200 nm, and the SIMS measurement was performed at a depth of 0 to 900 nm. Note that FIG. 3 shows only the measurement results at a depth of 0 to 200 nm. In addition, in FIG. 3, a depth of 0 nm indicates the surface 11 of the composite material 1. This is also the same in FIG. 4 described later. The measurement conditions for XPS and SIMS are as follows.

[0068] (XPS measurement conditions) Analytical equipment: ULVAC-PHI X-ray photoelectron spectrometer "PHI Quantera II" X-ray source: Monochrome AlKα Sputtering ions: Ar + Acceleration voltage: 4kV

[0069] (SIMS measurement conditions) Analyzer: Secondary ion mass spectrometer “D-SIMS 6650” manufactured by ULVAC-PHI Primary ion species: Cs + Secondary ion polarity: Negative Acceleration voltage: 2 kV Beam current: 25nA Charge compensation: None Raster size: 400μm

[0070] The measurement results revealed that in Example 1, the maximum value of the fluorine concentration was located at a depth of 90 nm. The maximum value of the fluorine concentration in Example 1 was 63 atomic %. It was revealed that in Example 2, the maximum value of the fluorine concentration was located at a depth of 46 nm. The maximum value of the fluorine concentration in Example 2 was 11 atomic %.

[0071] The area from a depth of 0 nm (surface 11) to a depth where the fluorine concentration becomes 1 ppm was defined as a first region 12, and the thickness T of the first region 12 was measured. The measurement results are as follows. (Thickness of the first region T) Example 1: 740 nm Example 2: 390 nm

[0072] FIG. 4 is a graph showing the results of hardness measurements in Example 1, Example 2 and Comparative Example 1.

[0073] (hardness) The hardness was measured by a nanoindentation method (based on ISO 14577). Here, the measurement was performed at a depth of 0 to 1000 nm. Note that FIG. 4 only shows the measurement results at a depth of 0 to 500 nm.

[0074] The hardness was measured under the following conditions. Measurement device: "Nanoindenter XP" manufactured by MTS Systems Measurement mode: Continuous stiffness measurement Indentation depth: Maximum 1000 nm Hardness unit: Vickers hardness

[0075] From the measurement results, it was revealed that in Example 1, the maximum value of hardness was located at a depth of 70 nm. The maximum value of hardness in Example 1 was 5 GPa. It was revealed that in Example 2, the maximum value of hardness was located at a depth of 20 nm. The maximum value of hardness in Example 2 was 7 GPa.

[0076] (Crystal structure) The crystal structure was evaluated by TEM, XRD, and XPS. In each of the measurements of TEM, XRD, and XPS, the first region 12 was determined from the thickness T of the first region 12, and the region located inward from the first region 12 was determined as the second region.

[0077] The TEM measurement conditions are as follows. Analytical equipment: FEI transmission electron microscope "Talos F200X" Acceleration voltage: 200 kV Beam current: 150pA Measurement location: Cross section of composite material 1 cut in the thickness direction

[0078] The measurement conditions for XRD are as follows. Analytical equipment: PANalytical's "X' Pert PRO-MRD" Tube:CuKα Incident angle: 0.5° Measurement range: 10~120°

[0079] The conditions for the XPS measurement were the same as those for the fluorine concentration described above.

[0080] First, a cross-section was observed by TEM. The diffraction patterns were referenced from a database provided by the International Centre for Diffraction Data (ICDD) (TiOF2: ICDD No. 00-008-0060, titanium α phase: ICDD No. 00-044-1294). As a result of the observation, in both Example 1 and Example 2, TiOF 2 A diffraction pattern belonging to (crystalline phase 2) was obtained, and a diffraction pattern of titanium α-phase (second phase 32) was obtained within the second region.

[0081] In both Example 1 and Example 2, the first phase 31 was confirmed in the first region 12. In Example 1, the crystal phase 2 was confirmed to be more abundant than the first phase 31. In Example 2, the first phase 31 was confirmed to be more abundant than the crystal phase 2. In Example 1, the amorphous phase 4 and the mixed phase 5 were confirmed in the first region 12.

[0082] Next, measurement was performed by XRD. For the diffraction pattern, JCPDS provided by ICDD was referenced. As a result of the measurement, it was confirmed that the first region 12 had a crystal structure different from that of the second region.

[0083] Then, measurement was carried out by XPS. The peak assignments are shown in Table 1. As a result of the measurement, in both Example 1 and Example 2, TiF 3 , TiF 4 and F-TiO 2 A peak attributed to the Ti-F-Ti bond was obtained in Example 1. This peak is considered to be due to titanium fluoride crystals. The other conditions shown in FIG. 1 were confirmed.

[0084] [Table 1]

[0085] (antibacterial) The antibacterial properties were measured by a film adhesion test (based on JIS Z 2801) using Staphylococcus aureus.

[0086] The measurement results are as follows. Adherent viable bacteria count (CFUs) Example 1: <10 (below detection limit) Comparative Example 1: 17667

[0087] As a result of the measurement, the number of attached live bacteria was below the detection limit in Example 1. In addition, the antibacterial activity value of Example 1 was 3.2. Therefore, it was clear that Example 1 had an antibacterial effect. [Explanation of symbols]

[0088] 1...Composite material 2. Crystal Phase of Titanium Fluoride 3. Metallic Crystal Phase of Titanium 31...Phase 1 32...2nd phase 4. Amorphous phase 5...Mixed phase 11...Surface 12...1st area 12a...Central part T Thickness A: Thickness direction 13...Second area 100···Dental Implants 101···Fixture 102 Abutment 103 Artificial teeth

Claims

1. A titanium and fluorine composite phase having, in order from the surface, a titanium fluoride crystalline phase and a first phase which is a fluorine-containing titanium metal crystalline phase, and having a fluorine concentration of 1 ppm or more; A composite material, wherein in a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located, the maximum value of the fluorine concentration is located at a depth of 20 nm or more and 100 nm or less.

2. The composite material of claim 1 , wherein the composite phase has an amorphous phase comprising titanium and fluorine.

3. 3. The composite material of claim 2, wherein the composite phase comprises a mixture of the amorphous phase, the titanium fluoride crystalline phase, and the metal crystalline phase.

4. The composite material described in claim 3, wherein the first phase is located on the surface side.

5. The composite material according to claim 4 , wherein, when a cross-sectional observation is performed by a TEM, the amount of the crystalline phase present in the composite phase is greater than that of the first phase.

6. 2. The composite material according to claim 1, wherein in a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located, the maximum value of the fluorine concentration is located at a depth of 50 nm or more and 100 nm or less.

7. 2. The composite material according to claim 1, wherein in a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located, a maximum value of fluorine concentration is located in the composite phase.

8. 2. The composite material according to claim 1, wherein in a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located, a slope of the spectrum of the fluorine concentration at a position 10 nm deeper from the maximum value of the fluorine concentration is larger than a slope of the spectrum of the fluorine concentration at a position 10 nm shallower from the maximum value of the fluorine concentration.

9. 2. The composite material according to claim 1, wherein a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located has a region deeper than a depth where a maximum value of the fluorine concentration is located, the region having a lower fluorine concentration than the fluorine concentration at the surface.

10. 2. The composite material according to claim 1, wherein a spectrum obtained by XPS analysis in a depth direction from a surface where the composite phase is located has a region where the fluorine concentration is less than 1 ppm only in a region deeper than a depth where a maximum value of the fluorine concentration is located.

11. 2. The composite material according to claim 1, wherein when the hardness is measured by nanoindentation in a depth direction from a surface where the composite phase is located, the maximum hardness value is located at a depth of 20 nm or more and 100 nm or less.

12. 12. The composite material of claim 11, wherein the hardness maximum is located at a depth of ≧50 nm and ≦100 nm.

13. 12. The composite material according to claim 11, having a maximum hardness of 3 to 10 GPa.

14. 12. The composite material according to claim 11, having a maximum hardness of 5 to 10 GPa.

15. The composite material of claim 1 having an oxide coating located on the surface.

16. The composite material according to claim 15, wherein the oxide film has a thickness of 2 to 5 nm.

17. 2. The composite material according to claim 1, wherein, when the fluorine concentration is measured in a depth direction from a surface where the composite phase is located, the depth at which the fluorine concentration is 1 ppm or more is 30 nm or more and 800 nm or less.

18. A biological implant comprising the composite material according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • SURFACE MODIFYING METHOD FOR IMPARTING HIGH TEMPERATURE OXIDATION RESISTANCE TO Ti-Al BASED ALLOY

    JP2002332569A

  • Methods for treating implants and implant surfaces

    JP2005533551A

  • Titanium material and living body implant

    JP2017101275A

  • Surface treatment method for metal materials and fluorine treatment mold

    JP4568396B2

  • Composite material and bioimplant

    WO2019230871A1